Household activity sytems, as a set of locational factors which could be used in preparing a barangay community concept diagram for the municipality of Santa Rosa, Laguna - Ajoku, Godwin O. (1988)
The study was conducted on household members of the residential area of Barangay 1 (Kanluran), and barangay 2 (Malusak), with the intention of identifying: existing and preferred activity systems, residential dwelling unit qualities (both existing and preferred), and finally, the needs and attitudinal factors associated with existing and preferred aspects. A knowledge on these aspects was necessary, for the development of a barangay concept diagram, for the municipality of Santa Rosa. It stresses the vital role of household activity systems, as a basis for the planning of a well-conceptualized residential community, which will ensure and foster livability standard of residents. Livability, as used here, refers to those qualities in the physical environment of the residential areas and surrounding urban areas which tend to induce in the citizens a feeling of mental, physical and social well-being according to the extent to which their fundamental day-to-day living needs and wants are satisfied.